Perancangan Sista (Sistem Informasi Orang Tua Mahasiswa) Pada Universitas Katolik St.Thomas Dengan Metode RAD (Rapid Application Development) - Harianja, Andy Paul; Sihotang, Jordan (LPPM UNIKA Santo Thomas Medan, 2022)
Parents have a very important role in the education of their children, especially for parents who have children at the university level. Many think that a child who has entered the world of lectures is independent, but the role of parents is still important. In academic activities carried out by students, not all parents know the activities carried out by their children, even though parents need to know the development of their children at the University so that parents can direct and support their children's lectures. Therefore, so that parents know information about their children, it is necessary to create a SISTA (Parent Student Information System) at the Catholic University of Santo Thomas as an information medium for parents of students of the Catholic University of Santo Thomas so that parents can monitor and control students.